PTH-081 Colorectal cancer in inflammatory bowel disease – is surveillance working?. (22nd June 2015) - Akbar, T; Rahmany, S; Harris, R; Cotton, S; McCabe, L-A; Lloyd, DA; Gordon, JN
Abstract : Introduction: The burden of colorectal cancer (CRC) in inflammatory bowel disease (IBD) is currently unclear. Recent studies suggest the magnitude of risk may be considerably lower than previous estimates raising questions surrounding current surveillance protocols. However, studies that use IBD surveillance cohorts to identify cases may underestimate the burden of disease with substantial number of cases arising in patients that fall outside current surveillance parameters. Our aim was to identify all cases of CRC arising in patients with IBD in a single geographic locality in a recent timeframe and analyse factors affecting diagnosis with particular reference to current UK surveillance recommendations. Method: Patients with IBD who developed CRC in a 5-year period from between 2010 and 2015 were identified from a fully maintained database of all CRC cases diagnosed in our locality. This was cross-referenced with histology reports and endoscopy reports from the same period. Case notes were reviewed with data on demographics, disease, presentation, diagnosis, CRC surveillance, cancer stage and outcomes collected and analysed. Results: 672 cases of CRC were identified in the study period of which 17 (2.5%) arose in patients with IBD (10 UC: 6CD: 1 IBDU). 16 cases were adenocarcinomas with 1 anal squamous cell carcinoma in a patient with longstanding fistulating perianal Crohn's disease. 6/17 cases (35%) were screen detected in asymptomatic patients undergoing regular surveillance. 4/17 (24%) were interval cancers identified in patients prior to their next scheduled surveillance. The remaining 7/17 (41%) were identified in patients who were not participating in a screening programme. 4 of these cases fell outside current screening parameters with the further 3 cases arising in patients who had ceased surveillance (average age 87; range 84–93). Surveillance in the interval cancers did not adhere to published guidelines in 3 out of 4 cases. 5/6 (83%) screen detected cases were classified as Duke's A or B, compared with 5/11 (45%) of the non-screen detected cases. Conclusion: The burden of CRC in patients with IBD is significant accounting for 2.5% of all cancers in the study period. Screen detected cancers were identified at an earlier stage than non-screen detected cancers, though 41% of cases arose in patients that would not currently qualify for screening in the UK. Screening did not adhere to guidelines in 75% of interval cancers. These results support the concept of a surveillance programme though reinforce the importance of meticulous high quality colonoscopy and adherence to guidelines to improve outcomes. Disclosure of interest: None Declared.